Role of Fusobacterium nucleatum-oral keratinocyte interactions in the progression of oral dysplasia and Oral Squamous Cell Carcinoma - Selvaraj, Ajith Kumar (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2023)
Dysplastic changes of the oral epithelium have a potential for malignant transformation. Several studies have identified increased abundance of Fusobacterium spp. on malignant and premalignant oral lesions. The potential role of Fusobacterium spp. in oral malignancy and its interaction with oral cells is poorly characterised. Oral malignancy is associated with the loss of epithelial biomarkers such as E-cadherin in dysplastic events and in the current study we examined the interaction of Fusobacterium spp. with E-cadherin positive and negative oral keratinocytes. For these analyses, we investigated the interaction of a type strain ATCC10953/NCTC10562 and clinical isolates of F. nucleatum subsp. polymorphum with oral cells. In our hands, traditional antibiotic protection assays to measure invasion were unable to discriminate internal and external bacteria, which lead us to develop a novel confocal microscopy-based assay to measure bacterial invasion. Epithelial cells were negatively stained with fluorescein and internalised bacteria were visualised using propidium iodide staining. Cells were scanned with a Leica confocal microscope and the images were analysed using Imaris image analysis software. Using this assay, we showed that F. nucleatum subsp. polymorphum type strain ATCC10953/NCTC10562 is highly adherent and invasive to E-cadherin expressing H357 oral keratinocytes. Clinical isolates of F. nucleatum subsp. polymorphum (n=7) were generally less adherent and invasive to E-cadherin expressing H357 compared to the type strain ATCC10953. Conversely, when E-cadherin negative H376 cells were used, clinical isolates exhibited greater adherence and invasion compared to the type strain ATCC10953. These data show that clinical isolates of F. nucleatum subsp. polymorphum adhere to and invade oral keratinocytes using E-cadherin independent mechanisms. Furthermore, we also demonstrate the effects of F. nucleatum subsp. polymorphum on cellular responses. OSCC cell motility, migration, invasion and the ability to form new blood vessels were increased in the presence of active F. nucleatum subsp. polymorphum infection. These mechanisms were enhanced due to the increase in secretion of essential chemokines such as MCP-1/CCL2, RANTES/CCL5, IP-10, MCS-F and extracellular matrix proteinase such as MMP-9. The E-cadherin negative cells due to their EMT phenotype were more invasive and were far more motile and invasive when infected with F. nucleatum subsp. polymorphum strains. Infecting the OSCC cells with F. nucleatum subsp. polymorphum significantly enhanced the secretion of chemokine VEGF-A required for tube-like vessel formation in vitro. The over-expression of this chemokine in E-cadherin negative cells reflects the selective affinity of F. nucleatum subsp. polymorphum to E-cadherin negative and a possible EMT cell phenotype. In summary, loss of E-cadherin expression in an early event in oral dysplasia, suggesting that dysplastic tissues may select microbiome constituents that adhere via E-cadherin independent mechanisms.
APPROVED